Waste-minimized synthesis of C2 functionalized quinolines exploiting iron-catalysed C–H activation. Issue 1 (10th December 2020) - Ferlin, Francesco; Zangarelli, Agnese; Lilli, Simone; Santoro, Stefano; Vaccaro, Luigi
Abstract : Herein we present an efficient and regioselective iron-catalyzed methodology for the external oxidant-free C–H activation of quinoline  N -oxide. Abstract : Herein we present an efficient and regioselective iron-catalyzed methodology for the external oxidant-free functionalization of quinoline- N -oxides. The protocol, based on the use of inexpensive and easily accessible FeSO4, showed broad applicability to a wide range of substrates. An additional green feature of this synthetic methodology is H2 O being the only by-product. Experimental and computational investigations provide support to a mechanism based on a facile C–H activation event. The green efficiency of the process has also been carefully assessed using: (i) metrics related to the synthetic process (AE, Yield, 1/SF, MRP and RME); (ii) safety/hazard metrics (SHZI and SHI); and (iii) metrics related to the metal used as the catalyst (Abundance, OEL and ADP). In addition to the many advantages of this protocol related to the green iron catalyst used and the safety/hazard features of the process, an E -factor value of ca. 0.92 (84 to >99% reduction compared to known protocols) evidently confirms the sustainable efficiency of the procedure presented. Practical utility has also been demonstrated by performing the reaction efficiently on a multi-gram scale.